Changes in survival and neurodevelopmental outcomes of infants born at - Yumi Kono; Naohiro Yonemoto; Hidehiko Nakanishi; Satoshi Kusuda; Masanori Fujimura (BMJ Publishing Group, 2018)
Objective To evaluate changes in the outcomes of infants born at <25 weeks' gestation in the past decade.Design Retrospective observational study.Settings A multicentre database of the Neonatal Research Network, Japan.Patients A total of 3318 infants born at 22-24 weeks' gestation between periods 1 (2003-2007) and 2 (2008-2012) from 52 tertiary centres.Main outcome measures We compared death and neurodevelopmental impairments (NDIs) at 3 years of age, including cerebral palsy (CP), visual impairments (VIs), hearing impairments (HIs) and the developmental quotient (DQ) of the Kyoto Scale of Psychological Development test <70, between two periods using multivariate logistic regression analyses adjusted for the centre, gender, multiple gestation, maternal age, caesarean delivery, antenatal steroid use, pregnancy-related hypertension, clinical chorioamnionitis, congenital anomalies and birth weight.Results A total of 496/1479 infants (34%) in period 1 and 467/1839 (25%) in period 2 died by 3 years of age (adjusted OR 0.70, 95% CIs 0.59 to 0.83). Follow-up data were collected from 631 infants (64% of survivors) in period 1 and 832 (61% of survivors) in period 2. The proportions of CP with Gross Motor Function Classification System ≥2, VI and HI in the infants evaluated were lower, while that of DQ <70 was higher in period 2 than in period 1. Using multiple imputations to account for missing data, death or NDI decreased from 54% in period 1 to 47% in period 2 (0.83, 0.71 to 0.97). Significant decreases were observed in death or CP (0.65, 0.55 to 0.76), death or VI (0.59, 0.50 to 0.69) and death or HI (0.69, 0.58 to 0.81), but not in death or DQ <70 (0.91, 0.78 to 1.06).Conclusion Along with improved survival, CP, VI and HI, but not cognitive impairments decreased in infants born at <25 weeks' gestation between the two periods examined in the last decade. Further strategies are needed to reduce cognitive impairments in these infants.